Personality Traits in Fibromyalgia: Aggravators and Attenuators of Clinical Symptoms and Medication Use - Dolores Santiago; Casandra I. Montoro; Dmitry M. Davydov; Gustavo A. Reyes del Paso (Behavioural Neurology)
Conclusion: Higher neuroticism and lower extraversion primarily increase the likelihood of using mood-regulating medications, but not analgesic drugs. Implementing coping strategies aimed at reducing neuroticism and enhancing extraversion may help to reduce medication use in patients with FMS.